PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN PENDIDIKAN FIP IKIP PGRI MADIUN - Hartini, Hartini; Gunawan, Imam; Nurina Suraya, Selly (Jurnal Pendidikan, 2012)
Education   service   quality very irrespective   influence   that given from a service user expectation with that perception  by service user. One of the factor that determine  customer  satisfaction  service quality    that    consist    of   five    service    dimensions:     reliability, responsiveness,   assurance,  empathy, and tangible.  Education  service quality  baseds  on from  human  resource  that  is lecturer,  staff,  and facilities.   This  research   aim detects  student  university   perception towards  education  service  quality  FIP IKIP PGRI  MADIUN.  This research uses to approach   quantitative as a mean to analyze difference between perception and expectation student  university towards education service. This research is done to describe service quality and student university     satisfaction      level.    Research respondent   as  much  as  293  student     niversities   from   total   1099 student   universities.    Sample  taking   uses   technique    proportional random  sampling.  Research  data is got by using closed model inquiry instrument.  Data analysis  technique  that used:  descriptive  analysis; analysis   of  variance;   and  analysis   performance    and  importance matrix.   Research   result  shows  that:  (1)  level  expectation   student university  about  education  service  quality  belongs  in category  very high; (2) student university  perception  level about education service quality  belongs  in high  category;  and (3) there  difference  between expectation        and   student   university    perception    about   education service quality.Key words:  Education Service Quality, Expectation,  Perception